Cultural dimensions of indigenous participation in education and training - Dockery, Alfred Michael (National Centre for Vocational Education Research Ltd, 2009)
The preservation of Indigenous cultures is a controversial issue in Australia. On the one hand, themaintenance of traditional Indigenous culture has been viewed as a barrier to integration withmainstream society and the achievement of socio-economic equality between Indigenous and non-Indigenous Australians. An alternative view sees maintenance of Indigenous culture to have a valuein its own right, and to be an integral component of any solution to the current plight of Indigenouspeople. If policy is to follow this latter view then it is important that economic and socialinstitutions can accommodate the different values and preferences associated with Indigenousculture.Despite the importance of these issues, there is very little empirical evidence on the link betweenIndigenous culture and socio-economic outcomes, including educational attainment. Two criticaland related empirical issues are whether Indigenous culture acts as a barrier to educationalattainment, and whether the existing education and training system adequately accommodates thecultural differences between Indigenous and non-Indigenous Australians. This research seeks toaddress these issues by explicitly measuring Indigenous culture and exploring the links betweencultural attachment and vocational education and training outcomes for Indigenous people, usingdata from the Australian Bureau of Statistics’ 2002 National Aboriginal and Torres Strait IslanderSocial Survey.The results suggest that, in non-remote areas, cultural attachment is complementary with botheducational attainment and participation in vocational training. Given the importance afforded toeducation as a means to addressing Indigenous disadvantage, this rejects the view underpinning thepolicies of assimilation that there is a trade-off between cultural maintenance and the achievementof mainstream socio-economic outcomes. From an equity perspective, the results also reflectpositively on the sensitivity of Australia’s education and training system to cultural needs. There isevidence both of education and training being pursued to enhance objectives relating to culturalmaintenance, and of cultural attachment itself having an enabling effect on Indigenous people.Lower access to education and training in more remote areas does, however, disproportionatelyimpact upon Indigenous Australians with stronger cultural attachment.